Do Workers Value Flexible Jobs? A Field Experiment - He, Haoran; Neumark, David; Weng, Qian (Journal of Labor Economics, 2021)
We explore workers’ valuation of job flexibility using a field experiment conducted on a Chinese job board. Our experimental job ads differ randomly in offering jobs that are flexible regarding when (time flexibility) or where (place flexibility) one works and in offering different salaries. Application rates are higher for flexible jobs conditional on the salary offered, providing evidence that workers value job flexibility. Moreover, under some plausible conditions our evidence is informative about job seekers’ willingness to pay for flexible jobs of the types offered in the experiment and points to fairly high valuation of the most flexible jobs.